2017
DOI: 10.1016/j.freeradbiomed.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

The impact of metagenomic interplay on the mosquito redox homeostasis

Abstract: Mosquitoes are exposed to oxidative challenges throughout their life cycle. The primary challenge comes from a blood meal. The blood digestion turns the midgut into an oxidative environment, which imposes pressure not only on mosquito fecundity and other physiological traits but also on the microbiota in the midgut. During evolution, mosquitoes have developed numerous oxidative defense mechanisms to maintain redox homeostasis in the midgut. In addition to antioxidants, SOD, catalase, and glutathione system, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 123 publications
(119 reference statements)
0
32
0
Order By: Relevance
“…[ 45 ] Similarly, the redox homeostasis system (thioredoxin, GSH peroxidase…) plays a vital role in the dynamics of symbiotic microbiota, which impacts Plasmodium transmission. [ 46 ] This would result in important implications for the design of strategies aiming at interfering with the GSH redox‐system of the mosquito. [ 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ] Similarly, the redox homeostasis system (thioredoxin, GSH peroxidase…) plays a vital role in the dynamics of symbiotic microbiota, which impacts Plasmodium transmission. [ 46 ] This would result in important implications for the design of strategies aiming at interfering with the GSH redox‐system of the mosquito. [ 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…The female mosquito gut is characterized by slightly acidic pH with a tendency to alkalinity after blood meals, a small volume, and frequent nutritional fluctuations (41). Iron availability contributes importantly to the assemblage of microorganisms in the mosquito midgut (3, 19, 42). Bacterial inhabitants of the adult mosquito midgut experience extreme conditions with relationship to iron availability, either having insufficient supply prior to and between blood meals, or excessive free iron and associated free radicals during and after blood meals (42, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Iron availability contributes importantly to the assemblage of microorganisms in the mosquito midgut (3, 19, 42). Bacterial inhabitants of the adult mosquito midgut experience extreme conditions with relationship to iron availability, either having insufficient supply prior to and between blood meals, or excessive free iron and associated free radicals during and after blood meals (42, 43). Our results showed that E. anophelis , a commensal organism of the mosquito midgut, responds to these extreme conditions and utilizes multiple iron uptake pathways, TBDTs, and iron chelating proteins in response to iron stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, their antimicrobial role, AMPs are also involved in chemotaxis and redox homeostasis with rapid radical scavenging ability (Cole et al, 2003;Com et al, 2003;Ganz, 2002;Liu et al, 2010;Zhao et al, 2011). Recently, the metagenomic approaches are extensively reviewed to explore the role of AMPs in redox homeostasis (Champion and Xu, 2017).…”
Section: Antiparasiticmentioning
confidence: 99%